Acculturation of Islamic Culture in Reog Ponorogo Art - Muhammad Fajar Pramono; Muhammad Handri Aris Saputro (Javanologi: International Journal of Javanese Studies, 2024)
One version of the history of Art Reog Ponorogo that has appeared in Ponorogo since the days of the Wengker Kingdom, in which the kingdom still adheres to Hindu-Buddhist beliefs, With the passage of time and the spread of Islam to the Ponorogo area, brought by Raden Bathoro kathong and accompanied by various teachings, cultures, and religious dogmas, there was a process of shifting and acculturation of the ritual traditions and customs of the Ponorogo people from Hindu-Buddhist teachings to Islamic teachings gradually. This study aims to determine the process of acculturation of Islamic culture to the art of Reog Ponorogo and to know the supporting factors, opportunities, and constraints. The method used in this research is grounded research. The results of this study show that the process of acculturation of Islamic culture in the Reog Ponorogo art began with the spread of Islam in Ponorogo brought by Raden Batoro Katong, and this process runs very smoothly and can coexist between Islamic culture and Reog Ponorogo art. The existence of supporting factors in the form of the number of existing Islamic institutions and the majority of people who have embraced Islam led to the opportunity of the acculturation process being very large, and obstacles that hinder the process are the limited funds for the procurement of art components (Reog Ponorogo).